2008
DOI: 10.1128/ec.00206-08
|View full text |Cite
|
Sign up to set email alerts
|

Protein Import into Hydrogenosomes ofTrichomonas vaginalisInvolves both N-Terminal and Internal Targeting Signals: a Case Study of Thioredoxin Reductases

Abstract: The parabasalian flagellate Trichomonas vaginalis harbors mitochondrion-related and H 2 -producing organelles of anaerobic ATP synthesis, called hydrogenosomes, which harbor oxygen-sensitive enzymes essential to its pyruvate metabolism. In the human urogenital tract, however, T. vaginalis is regularly exposed to low oxygen concentrations and therefore must possess antioxidant systems protecting the organellar environment against the detrimental effects of molecular oxygen and reactive oxygen species. We have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 55 publications
5
67
0
Order By: Relevance
“…Many hydrogenosomal proteins are equipped with a short N-terminal hydrogenosomal targeting signal (HTS), which directs the preprotein to the organelle (11). Recently, though, the first proteins were identified that are apparently imported based on internal targeting signals (53). This could help to explain the discrepancy between the number of proteins estimated to be present in the hydrogenosome (about 500) (73) and those that harbor an HTS (about 220) (11).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Many hydrogenosomal proteins are equipped with a short N-terminal hydrogenosomal targeting signal (HTS), which directs the preprotein to the organelle (11). Recently, though, the first proteins were identified that are apparently imported based on internal targeting signals (53). This could help to explain the discrepancy between the number of proteins estimated to be present in the hydrogenosome (about 500) (73) and those that harbor an HTS (about 220) (11).…”
Section: Discussionmentioning
confidence: 74%
“…The current estimate is significantly lower than the ϳ500 proteins expected to be found in the hydrogenosome (73). This is compounded by the finding that some HTS-lacking proteins are imported into hydrogenosomes, the alpha subunit of succinyl-coenzyme A (CoA) synthetase (TVAG_165340), and a thioredoxin reductase isoform (TVAG_125360) (53). Thus, protein properties in addition to an HTS are likely to serve as potential targeting precursors to the hydrogenosomes.…”
mentioning
confidence: 56%
See 3 more Smart Citations